Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
g (x) = -3^2 + 4x - 2
g (1) = -3^2 + 4(1) - 2
= - 9 + 4 - 2
= -5 -2
g (1) = - 7
g (1) = -3^2 + 4(1) - 2
= - 9 + 4 - 2
= -5 -2
g (1) = - 7
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.